On quasi-(2,n)-ideals of commutative rings - Bouba, El Mehdi; El-Khabchi, Yassine; Erdemir, Dilara; Koc, Suat; Tekir, Uensal (WORLD SCIENTIFIC PUBL CO PTE LTD, 2026)
Let A be a commutative ring with nonzero identity and I a proper ideal of A. I is said to be a quasi-(2,n)-ideal if whenever root I is a (2,n)-ideal of A. In this paper, we aim to give the relations between quasi-(2,n)-ideals and other classical ideals such as (2,n)-ideals, n-ideals and 2-absorbing quasi-primary ideals. In addition to give many properties, characterizations and examples of this new class of ideals, we also characterize some important class of rings such as UN-rings, reduced rings with at most two minimal prime ideals, integral domains, direct product of two integral domains in terms of quasi-(2,n)-ideals.
Keywords: n-ideal; (2, n)-ideal; quasi-(2, n)-ideal; PRIMARY IDEALS; Mathematics